2019
DOI: 10.3389/fgene.2018.00717
|View full text |Cite
|
Sign up to set email alerts
|

FLOating-Window Projective Separator (FloWPS): A Data Trimming Tool for Support Vector Machines (SVM) to Improve Robustness of the Classifier

Abstract: Here, we propose a heuristic technique of data trimming for SVM termed FLOating Window Projective Separator (FloWPS), tailored for personalized predictions based on molecular data. This procedure can operate with high throughput genetic datasets like gene expression or mutation profiles. Its application prevents SVM from extrapolation by excluding non-informative features. FloWPS requires training on the data for the individuals with known clinical outcomes to create a clinically relevant classifier. The genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(54 citation statements)
references
References 46 publications
1
53
0
Order By: Relevance
“…We then applied the best settings previously found for BNB, MLP and RF methods using responder-equalized data for the new eleven datasets containing different proportions of treatment responders' and non-responders' samples. In addition, we also used linear SVM method ( Figure 1, Table 3) with penalty parameter C = 1 because our previous results [8] showed that C ≤ 1 minimizes the risk of overtraining for SVM. The output ML classifier quality metrics were obtained for these four methods, including AUC ( Figure 1a The application of FloWPS improved the classifier quality for these four ML methods, as the median AUC for the treatment response classifiers increased from 0.76-0.84 range to 0.83-0.89 ( Figure 1a-d, Table 3).…”
Section: Performance Of Flowps For Non-equalized Datasets Using Bnb mentioning
confidence: 99%
See 4 more Smart Citations
“…We then applied the best settings previously found for BNB, MLP and RF methods using responder-equalized data for the new eleven datasets containing different proportions of treatment responders' and non-responders' samples. In addition, we also used linear SVM method ( Figure 1, Table 3) with penalty parameter C = 1 because our previous results [8] showed that C ≤ 1 minimizes the risk of overtraining for SVM. The output ML classifier quality metrics were obtained for these four methods, including AUC ( Figure 1a The application of FloWPS improved the classifier quality for these four ML methods, as the median AUC for the treatment response classifiers increased from 0.76-0.84 range to 0.83-0.89 ( Figure 1a-d, Table 3).…”
Section: Performance Of Flowps For Non-equalized Datasets Using Bnb mentioning
confidence: 99%
“…In turn, agnostic drug scoring approach, including machine learning (ML) methods can offer even a wider spectrum of opportunities by non-hypothesis-driven direct linkage of specific molecular features with clinical outcomes, such as responsiveness on certain types of treatment [7,8]. ML has a variety of methods that could be used for such agnostic approach, e.g., decision trees, DT [9,10], random forests, RF [11], linear [12], logistic [13], lasso [14,15], and ridge [16] regressions, multi-layer perceptron, MLP [10,17,18], support vectors machines, SVM [9,10,19], adaptive boosting [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations